An observational method to code concussions in the National Hockey League (NHL): the heads-up checklist. Issue 2 (13th June 2013) - Hutchison, Michael G; Comper, Paul; Meeuwisse, Willem H; Echemendia, Ruben J
Abstract : Background: Development of effective strategies for preventing concussions is a priority in all sports, including ice hockey. Digital video records of sports events contain a rich source of valuable information, and are therefore a promising resource for analysing situational factors and injury mechanisms related to concussion. Aim: To determine whether independent raters reliably agreed on the antecedent events and mechanisms of injury when using a standardised observational tool known as the heads-up checklist (HUC) to code digital video records of concussions in the National Hockey League (NHL). Methods: The study occurred in two phases. In phase 1, four raters (2 naïve and 2 expert) independently viewed and completed HUCs for 25 video records of NHL concussions randomly chosen from the pool of concussion events from the 2006–2007 regular season. Following initial analysis, three additional factors were added to the HUC, resulting in a total of 17 factors of interest. Two expert raters then viewed the remaining concussion events from the 2006–2007 season, as well as all digital video records of concussion events up to 31 December 2009 (n=174). Results: For phase 1, the majority of the factors had a κ value of 0.6 or higher (8 of 15 factors for naïve raters; 11 of 15 factors for expert raters). For phase 2, all the factors had a total percent agreement value greater than 0.8 and κ values of >0.65 for the expert raters. Conclusions: HUC is an objective, reliable tool for coding the antecedent events and mechanisms of concussions in the NHL.